Bioactive Compounds in Sea Buckthorn and their Efficacy in Preventing and Treating Metabolic Syndrome - Ying Chen; Yunfei Cai; Ke Wang; Yousheng Wang (Foods, 2023)
Sea buckthorn (Hippophae rhamnoides L. or Elaeagnus rhamnoides L.) is a plant that has long been used as a Chinese herbal medicine. This species is known to contain numerous bioactive components, including polyphenols, fatty acids, vitamins, and phytosterols, which may be responsible for its medicinal value. In experiments both in vitro and in vivo (ranging from cell lines to animal models and human patients), sea buckthorn has shown positive effects on symptoms of metabolic syndrome; evidence suggests that sea buckthorn treatment can decrease blood lipid content, blood pressure, and blood sugar levels, and regulate key metabolites. This article reviews the main bioactive compounds present in sea buckthorn and discusses their efficacy in treating metabolic syndrome. Specifically, we highlight bioactive compounds isolated from distinct sea buckthorn tissues; their effects on abdominal obesity, hypertension, hyperglycemia, and dyslipidemia; and their potential mechanisms of action in clinical applications. This review provides key insight into the benefits of sea buckthorn, promoting future research of this species and expansion of sea buckthorn-based therapies for metabolic syndrome.